"Listening is an act of love": Learning listening through StoryCorps. Issue 1 (2nd January 2016) - Simmons, Nathaniel; Tenzek, Kelly E.
Abstract : Courses: Interpersonal Communication, Basic Survey Course, Group Communication, Organizational Communication, Intercultural Communication, Listening, Family Communication, Interviewing, Business and Professional Communication. Objectives: After completing this single class activity, students will be able to: (a) define listening; (b) identify listening as a top skill employers desire; (c) explain how listening may be perceived as an act of love; and (d) critically assess ways in which their listening behaviors may be improved.